Depik, eas, dan relo; yang manakah Rasbora tawarensis? [Depik, eas, and relo; which one is Rasbora tawarensis?] - Z. A. Muchlisin (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2011)
There are at least three species of Rasbora known locally as depik, eas, and relo in Lake Laut Tawar. Morphological traits of the three species of Rasbora are very similar and difficult to distinguish. Therefore, there remains a great deal of taxonomic uncertainty as to which of three is Rasbora tawarensis the endemic fish in the lake, not only among the locals but also local fisheries agency and researchers. The precise identification of R. tawarensis is crucial to develop a better strategy for conservation effort of this endemic and threatened species. Here, we utilized a comprehensive approach by combining morphometric and genetic methods to discriminate among these group as defined by their local names in Lake Laut Tawar. Traditional morphometric and DNA sequencing of the mitochondrial cytochrome c oxidase subunit I (COI) were applied. The results showed that there are only two valid species of Rasbora among the group. The morphometrics and genetic data strongly indicated that eas and depik should be regarded as the same species of Rasbora tawarensis and relo may be considered as a cryptic species. AbstrakTiga kumpulan ikan Rasbora yang dikenali sebagai eas, depik, dan relo ditemukan di Danau Laut Tawar. Secara morfologi ketiga kumpulan ikan tersebut sangat mirip dan sepintas sulit dibedakan. Hal itu telah menyebabkan ketidakpastian taksonomik yang mana diantara ketiganya disebut Rasbora tawarensis. Identifikasi yang tepat perlu dilakukan dalam rangka konservasi ikan endemik ini. Pendekatan komprehensif digunakan dengan menggabungkan analisis morfometrik dengan analisis genetik untuk mendiskriminasikan tiga kumpulan Rasbora. Dalam penelitian ini digunakan morfometrik tradisional dan sekuen DNA dari sitokrom mitokondria c oxidase subunit I (COI). Hasil analisis menunjukkan adanya dua spesies Rasbora dalam kelompok. Data morfometrik dan genetik memperlihatkan bahwa eas dan depik adalah spesies yang sama, yaitu Rasbora tawarensis, sedangkan relo adalah spesies kriptik.